THE INFLUENCE OF ACUPUNCTURE THERAPY IN MODERN TIMES FOR OSTEOARTHRITIS TREATMENT: A LITERATURE REVIEW - Fikratul Aulia Puti; Abdullah, Dessy; Febianne Eldrian; Tati Khairina; Muhamad Ivan; Dhina Lydia Lestari (Nusantara Hasana Journal, 2024)
Background: Osteoarthritis (OA) is a degenerative joint disease affecting millions globally, characterized by pain, stiffness, and reduced mobility. While conventional treatments, such as nonsteroidal anti-inflammatory drugs (NSAIDs), physical therapy, and surgery offer symptomatic relief, they often have associated side effects and long-term risks. In contrast, acupuncture, a traditional Chinese medicine technique, has emerged as a popular alternative for OA management. Despite its extensive use, debates persist regarding the physiological mechanisms underlying acupuncture and its long-term efficacy. Methods: This literature review examines recent clinical studies and meta-analyses focused on acupuncture therapy for OA. The analysis involved selecting articles from respected databases, including PubMed, ScienceDirect, and Scopus, and concentrated on randomized controlled trials (RCTs), systematic reviews, and cohort studies published in the past decade. Results: The analysis reveals that acupuncture can significantly alleviate OA-related pain and enhance joint function. Research indicates that acupuncture facilitates the release of endorphins, modulates inflammatory responses, and improves blood circulation in the affected joints. Notably, electroacupuncture, an advanced form of traditional acupuncture, has shown superior effectiveness in relieving OA symptoms. However, the diversity in study designs, acupuncture methods, and individual patient reactions creates challenges in formulating standardized treatment protocols. Conclusion: Acupuncture emerges as a promising complementary therapy for OA, providing pain relief and improved mobility with minimal side effects. Nevertheless, additional high-quality research is essential to establish comprehensive treatment protocols, verify long-term benefits, and incorporate acupuncture into evidence-based medical practice.